Sustained intraocular vascular endothelial growth factor neutralisation does not affect retinal and choroidal vasculature in Ins2Akita diabetic mice. (September 2019) - Lechner, Judith; Hombrebueno, Jose R; Pedrini, Edoardo; Chen, Mei; Xu, Heping
The purpose of this study was to understand the influence of sustained intravitreal vascular endothelial growth factor neutralisation on the retinal and choroidal vasculature in diabetic eyes. Ins2 Akita diabetic mice received five intravitreal injections of anti-mouse vascular endothelial growth factor antibody or goat immunoglobulin G (0.2 µg/µL/eye) over a 4-month period. Retinal and choroidal vascular changes were analysed by confocal microscopy of tissue flat-mounts. Retinal gene expression of vascular endothelial growth factor family members (vascular endothelial growth factors A, B, C and D), vascular endothelial growth factor receptors (sVEGFR-1 and VEGFR-2) and tight junctions (claudin 1, 2, 5; occludin and zonula occludens-1) were analysed by quantitative reverse transcription polymerase chain reaction. Vascular endothelial growth factor A and claudin 5 were significantly increased in diabetic retinae. Gene expression was unaffected by anti-vascular endothelial growth factor treatment. The number of acellular vessels was increased in diabetic retinae and reduced following anti-vascular endothelial growth factor treatment. Retinal and choroidal vascular density and area were unaffected by sustained vascular endothelial growth factor neutralisation. Our results suggest that five consecutive intravitreal anti-vascular endothelial growth factor injections do not cause significant vascular changes in the retina and choroid in diabetic and non-diabetic mice.